Nutrition and performance - Spesific consideration on young female cross-country skiers - Kettunen, O. (University of Jyväskylä, 2022)
CONCLUSIONS • Mean energy availability is moderate but suboptimal o Only few individuals have optimal EA ("geen light") o Some individuals have significant difficulties o Athletes have more optimal eating practices at camp where meals were served from buffet in prescheduled times • Protein and fat intake are in line with the recommendations, but adequate carbohydrate intake is a major challenge • Adequate energy and carbohydrate intake may help to maintain performance and avoid overreaching during hard training periods o Note! Low hearth rate and blood lactate are not automaticly a good sign ? important to consider in relation to the feelings of an athlete o Maintaining adequate neuromuscular capasity during training camp is important as it is needed for high quality cross-coutry ski training • Adequate nutrition knowledge and arrangements that reduce athletes own responsibility to plan, schedule and prepare the meals may help young athletes to meet recommended levels of energy availability and carbohydrate intake Education!